The other significant others : reimagining Life with Friendship at the Center - Cohen, Rhaina, ....- (New York : St. Martin's Press, 2024)
Why do we assume romantic relationships are more important than friendships? What do we lose when we expect a spouse to meet all our needs? And what can we learn about commitment, love, and family from people who put deep friendship at the center of their lives? In The Other Significant Others, NPR's Rhaina Cohen invites us into the lives of people who have defied convention by choosing a friend as a life partner―these are friends who are home co-owners, co-parents or each other’s caregivers. Their riveting stories unsettle widespread assumptions about relationships, including the idea that sex is a defining feature of partnership and that people who raise kids together should be in a romantic relationship. Platonic partners from different walks of life―spanning age and religion, gender and sexuality and more―reveal how freeing and challenging it can be to embrace a relationship model that society doesn't recognize. And they show that orienting your world around friends isn't limited to daydreams and episodes of The Golden Girls, but actually possible in real life. Based on years of original reporting and striking social science research, Cohen argues that we undermine romantic relationships by expecting too much of them, while we diminish friendships by expecting too little of them. She traces how, throughout history, our society hasn’t always fixated on marriage as the greatest source of meaning, or even love. At a time when many Americans are spending large stretches of their lives single, widowed or divorced, or feeling the effects of the "loneliness epidemic," Cohen insists that we recognize the many forms of profound connection that can anchor our lives. A rousing and incisive book, The Other Significant Others challenges us to ask what we want from our relationships―not just what we’re supposed to want―and transforms how we define a fulfilling life.
Keywords: Relationship